The real experience of nurse role reconstruction under the implementation of the no-attendant care policy in Shanghai hospitals: a qualitative study - Cheng, Yuhan; Wan, Sibei; Jiang, Yifan; Sheng, Yi; Wu, Qian; Shi, Yan; Wang, Li (Frontiers in Health Services, 2025)
ObjectiveTo explore nurse role reconstruction under the implementation of no-attendant care services in Shanghai hospitals, and to identify challenges and strategies for optimization.MethodsA phenomenological qualitative design was adopted. From June 1 to July 1, 2025, semi-structured face-to-face interviews were conducted with 14 registered nurses from no-attendant care wards in three tertiary hospitals in Shanghai. Data were transcribed verbatim and analyzed using Colaizzi's seven-step method. Two researchers independently coded, discrepancies were resolved through discussion and methodological arbitration, and results were validated through member checking to ensure rigor.ResultsFour main themes and eleven subthemes were extracted: (1) Expanded Responsibilities and Intensified Workload: Significant Increase in Work Intensity; New Challenges in Professional Competence; Multidimensional Accumulation of Occupational Stress. (2) Positive Impacts on Patients and Families: Effective Relief of Family Care Burden; Enhanced Perceived Value of High-Quality Nursing. (3) Challenges in the Implementation Process: Blind Spots in Patient Safety Management; Need to Improve Nurse–Patient Communication Efficiency; Inadequate Mechanisms for Accountability. (4) Optimization Strategies: Establish a Legal Safeguard System; Improve Insurance Payment Coordination Mechanism; Strengthen Training Mechanisms for Nursing Assistants. A few minority or dissenting perspectives were incorporated as contextual modifiers.ConclusionNo-attendant care improves patient experience and alleviates family caregiving burden, but simultaneously places heavier physical, risk, and relational demands on nurses, highlighting the complexity of role reconstruction. This study demonstrates the essential features of nurses’ lived experiences under this model and emphasizes the need for systemic support, such as legal frameworks, insurance coverage, and workforce training, to optimize care delivery and sustain professional resilience.